Mutation detection in cholestatic patients using microarray resequencing of ATP8B1 and ABCB11 - McKay, Kirsten E (F1000Research, 2013)

(untitled)
Background : Neonatal cholestasis is a common presentation of childhood liver diseases and can be a feature of various conditions including disorders of bile acid biogenesis and transport, various inborn errors of metabolism and perinatal infections. Some inherited metabolic diseases can be easily screened using biochemical assays, however many can only be accurately diagnosed by DNA sequencing. Fluorescent capillary Sanger sequencing (FS) is the gold standard method used by clinical laboratories for genetic diagnosis of many inherited conditions; however, it does have limitations. Recently microarray resequencing (MR) has been introduced into research and clinical practice as an alternative method for genetic diagnosis of heterogeneous conditions. In this report we compared the accuracy of mutation detection for MR with FS in a group of patients with ‘low-normal’ gamma glutamyl transpeptidase (gGT) cholestasis without known molecular diagnoses. Methods : 29 patient DNA samples were tested for mutations in the ATP8B1 and ABCB11 genes using both FS and MR. Other known causes of “low gGT cholestasis” such as ARC syndrome and bile acid biosynthesis disorders were excluded. Results : Mutations were identified in 13/29 samples. In 3/29 samples FS and MR gave discordant results: MR had a false positive rate of 3.4% and a false negative rate of 7%. Conclusions : The major advantage of MR over FS is that multiple genes can be screened in one experiment, allowing rapid and cost-effective diagnoses.  However, we have demonstrated that MR technology is limited in sensitivity. We therefore recommend that MR be used as an initial evaluation, with FS deployed when genetic and clinical or histopathological findings are discordant.